Sami Tourism in Northern Sweden - Supply, Demand and Interaction - Pettersson, Robert (2004)
The thesis present the challenges and opportunities for indigenous tourism in Northern Sweden. The author provides with the large scope of information with regards to current development of Sami tourism industry.